Potensi Radikalisme di Perguruan Tinggi (Studi Kasus di Politeknik Negeri Balikpapan) - Basri Basri; Nawang Retno Dwiningrum (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
Today the noble values of the Pancasila begin to fade because of the growth of fanatical attitudes towards certain groups, the emergence of various kinds of organizations with particular groups even in the name of Islam. Islam which teaches the values of glory such as; love of peace, love, mutual respect between one another religion, but religion is sometimes interpreted according to his will by certain groups as a foundation in launching his mission by approaching religious teachings by means of violence and coercion. Radicalism which was only directed at a less educated group of people, has now fallen to educated groups or students in universities. Some university leaders have indicated the involvement of students in radical understanding on campus. Because of concerns about the emergence of radical understanding in higher education institutions a few months ago the Minister of Technology Research and Higher Education Prof. Dr. Mohammad Nasir gathered college leaders to declare against radicalism the campus. The purpose of this study is to further examine the potential of radicalism among Balikpapan State Polytechnic students, the object of this study is students especially students of internal organizational activists on campus or students of campus external organizational activists data collection techniques using questionnaires and interviews then the data is processed. The results of this study indicate the existence of radicalism among students. From data obtained, radicalism among students is not formed from internal campus but formed through the activities of external organizations that are outside the campus.  The existence of student affiliations with external campus organizations forms students into radicals which then enter the campus.